ANALISIS MINAT MEMBACA DENGAN MENGGUNAKAN CERITA BERGAMBAR PADA SISWA KELAS IIB SD NEGERI 001 SAMARINDA UTARA - Siska Oktaviani (SISTEMA: Jurnal Pendidikan, 2022)
This research was motivated by findings during the observation of the learning process carried out at SD Negeri 001 North Samarinda. It is known that when teaching in class there are some students who are less interested in reading and tend to be bored when paying attention to the teacher's explanation. As a result, researchers are interested in seeing the process of reading interest by using picture stories. The method used in this research is qualitative method. Class teachers, students and parents of class IIB students as resource persons in this study. The sampling technique used was purposive sampling. Interviews and documentation as data collection tools. Data analysis was carried out through data reduction, data presentation and conclusions. Testing the validity of the data using source triangulation. The results showed that the interest in reading by using picture story books was very large because with the pictures in the story books, it was easier for students to understand the meaning or content of the books they read.